2015
DOI: 10.1002/maco.201508255
|View full text |Cite
|
Sign up to set email alerts
|

Composition and corrosion protection of hexafluorozirconic acid treatment on steel

Abstract: In this study, steel samples treated in a hexafluorozirconic acid based solution for different durations were investigated. X-ray photoelectron spectroscopy (XPS) revealed the existence of a zirconium oxide (ZrO 2 ) layer on the treated steel. The increased contact angle of water on the treated steel with increased treatment duration indicated that the hexafluorozirconic acid treatment promoted the hydrophobicity of the surface. The corrosion results showed that the longer acid treatment gave rise to higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…On the other hand, the Zr-based treatment increases the corrosion potential in the delaminated area which can leads to a lower oxygen reduction rate, hence decreasing the hydroxyl ion formation at the delamination front in the cathodic region [18,48]. It is good to mention that the results presented here are in full agreement with the work of Khun et al who studied the effect of the hexafluorozirconic acid pretreatment on cathodic delamination of epoxy coating from carbon steel substrates and showed that the treatment can improve delamination and corrosion resistance of carbon steel at neutral pH, reporting this to be due to better interfacial adhesion [28,29].…”
Section: Skpsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the Zr-based treatment increases the corrosion potential in the delaminated area which can leads to a lower oxygen reduction rate, hence decreasing the hydroxyl ion formation at the delamination front in the cathodic region [18,48]. It is good to mention that the results presented here are in full agreement with the work of Khun et al who studied the effect of the hexafluorozirconic acid pretreatment on cathodic delamination of epoxy coating from carbon steel substrates and showed that the treatment can improve delamination and corrosion resistance of carbon steel at neutral pH, reporting this to be due to better interfacial adhesion [28,29].…”
Section: Skpsupporting
confidence: 82%
“…This is promising for industrial application aiming for a robust and reproducible process. Khun et al [28,29] studied the effect of hexaflurozirconic acid treatment on corrosion protection and adhesion strength of polyurethane and epoxy coatings applied on carbon steel and zinc showed that the Zr-based pretreatment resulted in enhanced corhttp://dx.doi.org/10.1016/j.porgcoat.2016.11.016 0300-9440/© 2017 Elsevier B.V. All rights reserved. rosion protection and adhesion performance of the organic coatings [34].…”
Section: Introductionmentioning
confidence: 99%
“…63 Volta potential profiles of the uncoated carbon steel and epoxy-coated steel with different pre-treatment time in Zr-conversion bath are presented in Fig. 13.…”
Section: Adhesion Strength and Delamination Mechanism Of The Substratmentioning
confidence: 99%
“…At shorter formation times (60 s), the TecTalis coating contained Cu, Cu 2 O and CuO. 63 At longer times (180 s) the content of CuO decreased, indicating that prolonged treatment promotes the formation of Cu 2 O in the ZrO 2 layer. The behavior on alloys can be different as discussed below.…”
mentioning
confidence: 96%
See 1 more Smart Citation